Atenção seletiva na aprendizagem da função seno com auxílio da realidade aumentada - Nascimento, Erinaldo Ferreira do (2023)
This study aimed to analyze the function of selective attention in the learning process of the sine function with the support of augmented reality. Education is permeated by changes that can happen as society changes. Thus, technologies are also being inserted in the educational scenario and in Mathematics Education, an area of knowledge that is present in human formation. One can already see their application in different contents, as well as the contributions of Cognitive Neuroscience to the teaching-learning process in schools. Thus, the development of the investigation took place under the methodological perspective of Classic Didactic Engineering (EDC) proposed by Artigue (1998), exploring two phases: preliminary analyzes and conceptions and a priori analysis. Following the phases, the study on epistemological obstacles was developed, based on the history of mathematics in the field of trigonometry. In the usual analysis, an overview of the behavior of the object under study - sine function - was made within the official documents that govern education, in addition to the analysis of the PNLD textbooks of 2018 and 2021 and a search, in the database, of research approaching that object. The theoretical bulge deepened in the knowledge about the Cognitive Neuroscience of Sternberg (2010); Gazzaniga et al. (2018); Cosenza and Guerra (2011); Lent (2002); Posner and Raichle (1994); Russian (2015); Fuentes (2001); Miller (2000); Benicasa (2013); with emphasis on the Theory of Integration of Features (TIC), Treisman and Gelade (1980). The Anthropological Theory of Didactics (TAD), advocated by Chevallard (2009) and Augmented Reality (AR), based on Caetano (2013); Azuma (2006); Schlemmer (2014). The second phase, the construction of the Didactic Sequence (DS), was divided into three stages, composed of activities/tasks. This sequence was not applied in the classroom, and the validation took place, based on the elaboration of an instrumental filter that included the activities/tasks, by the members of the neuroMATH research group. The tasks of the sine functions were elaborated within the perspective of exploring selective attention from the stimuli of the Theory of Integration of Features supported by GeoGebra with Augmented Reality in tests carried out during the validation of the SD. The results of the previous analyzes showed the importance of historical knowledge, official documents and theoretical notes to guide the construction of the didactic sequence. Thus, in the conception and a priori analysis, based on the validation of the didactic sequence, the results indicated that the use of Augmented Reality in activities develops the students' selective attention from visual and manipulable objects.